(untitled) (ModaPalavra e-periódico, 2024)
Based on a qualitative study, this work aims to understand the meaning of marriage as an institution and ritual for a group of women. Understanding that the wedding dress, as a material culture, is a fundamental element in the conception of the ritual, the question that arises, based on Kopytoff’s essay on the biography of things, is what happens to the dress after the ceremony? For the interviewed generation, women between 50-60 years old, marriage is an institution that inspires doubts and what happens to the dress has a close relationship with the history of each marriage and how each woman perceives the meaning of that institution.